Development of a PCR assay for rapid diagnosis of Mycobacterium ulcerans infection. - Ross, B C (1997)
The diagnosis of Mycobacterium ulcerans infection is hampered by the slow growth of the bacterium in culture, resulting in a delay of several months before a specific diagnosis can be obtained. In addition, M. ulcerans cannot be isolated from water even when there is convincing epidemiological evidence implicating this as the source of infection. The aim of the present study was to develop a PCR assay to circumvent the problems of delayed diagnosis and insensitivity of standard bacterial culture for M. ulcerans. For the PCR, we isolated an M. ulcerans-specific DNA fragment, 1,109 bp long, which is repeated at least 50 times throughout the genome. Use of this sequence as a target for PCR allowed us to detect as few as 2 molecules of genomic DNA in vitro. The PCR was used to detect M. ulcerans DNA in fresh tissue and paraffin-embedded sections from all seven patients with culture-confirmed cases of infection.